Framework Analysis Using The Rapid Evidence Assessment (REA) Method in Human Resources Information System Development - Dhimas Pamungkas Wicaksono; Chastine Fatichah (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2023)
The framework application in the first phase of the Human Resources Information System (HRIS) development at X Company, which is a mining company, has so far been considered to have encountered many problems, with bugs and defects frequently being found that occurred when the project was deployed to a production environment. This happens due to frequent changes in project requirements in the middle of the development process, so many features become less relevant to business systems. So making decisions quickly and precisely before the first phase ends is necessary. The Rapid Evidence Assessment (REA) method was taken because it is a rapid review, which only a few weeks can decide based on field objective evidence. The use of a questionnaire involving project members was compared with the literature review results, namely that five aspects affected the time to develop: organizational aspects, process aspects, project aspects, people aspects, and technical aspects. The Scrum framework is a framework that is much more relevant to the current project conditions, with 3.6-point results and 3.1 points for the waterfall.